APPLICATION OF VIRTUAL AND AUGMENTED REALITY IN TRAINING OF SOCIAL WORK SPECIALISTS - Polina Stavreva-Kostadinova (Science & Research, 2019)

(untitled)
The training of social work professionals is part of the lifelong learning practice. In the future, the learners participate in individual and group training sessions in virtual reality. Application of interactive methods the learners gradually adapt, analyse and apply communicative behavioural approaches to their clients without fear of mistakes. The application of a virtual environment with partial or full contact of the participant will create a perspective for the spectrum of emotions, experiences and experiences in the social work with vulnerable groups. The development of similar virtual games and simulations would be cost-effective, as it will minimize the so-called "professional" errors and inefficient behavioural decisions by social workers. Students will face different behavioural and communicative models, preparing their perceptions to respond adequately by taking part in the decisionmaking process of the client or the user. In learning conditions, learners in social work can analyse and develop their empathy, emotions and behaviour to improve their understanding of the process of social work with vulnerable groups. The study covers an assessment of the need and types of possible applications of a virtual environment for the training of social work professionals. An analytical approach to the problem has been applied through data from interviews and focus groups of students in the speciality “social work” and new specialists in social work are used.